Photobook phenomenon: an interview with Moritz Neumüller - João Queiroz (Imprensa da Universidade de Coimbra, 2021)
In this interview, Moritz Neumüller reflects on the nature of the photobook as a specific medium, and examines its place in contemporary photography. The interview was made by João Queiroz and Ana Luiza Fernandes in February and March 2021.